Penerapan Keselamatan dan Kesehatan Kerja Menggunakan Metode HIRARC pada Pemeliharaan Gardu Distribusi di ULP PLN Praya - Hardinata, Dhika Aufa; Adnyani, Ida Ayu Sri; Nrartha, I Made Ari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Praya Customer Service Unit (CSU), especially in the field of distribution substation and transformer maintenance, is engaged in providing maintenance of PLN distribution network assets in the electricity system. For the possibility of work accidents to occur, it is necessary to identify, analyze, and manage potential hazards and their control measures using the HIRARC method. The study found potential hazards with different categories such as repairing electrical substation installations with Extreme risk levels, controlling them by using complete Personal Protective Equipment (PPE), checking substation insulators with High risk levels, controlling them by using 20Kv safety gloves, measuring transformer voltage and current with a Moderate risk level (Moderate) control by checking measuring instruments, lifting equipment to the top of the transformer with a High risk level (High) control by checking the condition of the ladder regularly, and cleaning bushes around the transformer box with a Low risk level (Low) control by spraying insect repellent.